Pengaruh Perbedaan Tekanan Pengepresan terhadap Kualitas Briket Arang Kotoran Sapi - Eugenius Belarminus Siki; Oktovianus R. Nahak. T.B. (Program Studi Peternakan, Fakultas Pertanian, Universitas Timor, 2020)
This research has been carried out in the laboratory of the Faculty of Agriculture, University of Timor, lasting for one month from August 7, 2019 to September 5, 2019. The purpose of this study was to determine the effect of different pressures on the quality of cow manure charcoal briquettes. This study used a completely randomized design model (CRD) with 4 treatments and each treatment was repeated 4 times so that there were 16 experimental units. The composition of the briquettes is 95% cow dung and 5% starch while the treatments tested consist of: (R1) = cow dung briquette with a pressing pressure of 10 kg / cm2, (R2): Briquette manure briquettes with a pressing pressure of 20 kg / cm2, (R3): Cow dung briquettes with pressures of 30 kg / cm2 and (R4): Cow dung briquettes with pressures of 40 kg / cm2. Anova variance results showed that the parameters of water content and ash content did not show a real effect between treatments while the combustion rate and heat value showed a real effect between treatments (P <0.05).It was concluded that the best quality of briquettes was seen from the water content and the heating value was in treatment R3 (briquette manure briquettes with a pressing pressure of 30 kg /cm2), while for the best ash content and rate of combustion in treatment R2 (briquette manure briquettes with pressures of 20 kg / cm2).